Synthesis of Various Sulphonamide-Linked Fluoroquinolones as Antibacterial Agents - BHANU DEEPIKA, KANUMURI; SANMUGA PRIYA, EKAMBARAM; MURALI, KUMARASAMY; RAMESH KUMAR, NATESH (Asian Journal of Chemistry, 2010)
In the present study various derivatives of sulphonamide linked moxifloxacin were synthesized and their chemical structures were confirmed by means of elemental analysis and spectral data (IR, NMR and mass). These compounds were screened for antibacterial activity against Staphylococcus aureus ATCC 9144, Staphylococcus epidermidis ATCC 155, Bacillus cereus ATCC 11778, Pseudomonas aeruginosa ATCC 2853, Klebsiella pneumoniae ATCC 11298 and Escherichia coli ATCC 25922 by paper disc diffusion techniques. The minimum inhibitory concentrations (MIC) of the compounds were also determined by agar streak dilution method using the standard drug ciprofloxacin. All the compounds exhibited moderate to good antibacterial activity. The acute oral toxicity of the compounds were determined and found to be non-toxic at the dose of 2000 mg/kg. Selected compounds were screened for in vivo antibacterial activity by Mouse protection test.